Securing the EU's competitiveness and Resilience - Julio Saavedra (CESifo GmbH, 2025)
The European Union faces several simultaneous threats to its competitiveness: weakness in the industries of the future, insufficient innovation, expensive energy, the need to green its economy, and geopolitical and trade shifts, to name but a few. The EconPol Europe Annual Conference, on whose proceedings this policy brief is based, focused on three aspects that could make a substantial contribution to securing prosperity in the EU, but are in a lamentable state: they all currently fall far short of their potential. These are the power of the single market, the level of its innovation, and the capacity to defend itself. Both the high-level speakers at the conference as well as EconPol and ifo research make clear that some low-hanging fruit are there for the taking, if only the political will were there, a good dose of national chauvinism could be overcome, and an effective communication campaign were undertaken to explain to voters why some measures are not only necessary, but unavoidable.
Keywords: 330; Internationaler Wettbewerb; Resilienz; EU-Binnenmarkt; Innovation; Verteidigungsmanagement; EU-Staaten